PERKEMBANGAN PERILAKU SOSIAL REMAJA DI PANTI ASUHAN - WIJAYANTI, THERESIA; Hidayah, Nurul; Retnowati, Lucia (HOSPITAL MAJAPAHIT (JURNAL ILMIAH KESEHATAN POLITEKNIK KESEHATAN MAJAPAHIT), 2018)
Adolescence is a phase of dynamic development in the life of an individual. This period is a period of transition from childhood to adolescence marked by accelerating the development of physical, mental, emotional and social future take place in the second decade of life (Narendra et al, 2007) .In general, children feel inferior because they feel different from other children, they were not raised by their own family. The general objective of this research was to describe the development of role behavior of teenagers in Elim orphanage and Orphanage Christian Malang. which was held on June 27-28, 2016. This type of research is descriptive with a population of 58 teenagers. Using sampling total with a sample of 58 adolescents. The results showed 56, 90% had a brave and cowardly nature socially, 51.72% have properties could rejected and accepted socially, 58, 62% have a calm and quiet nature of social exclusion. All three of these variables had an important role in the formation of adolescent social behavior particularly in the development of role social behavior of teenagers in an orphanage. It was expected that teens can open up and be able to develop in accordance with the social behavior of adolescents with peers at home or outside the home and for health workers is expected to provide counseling to caregivers at the orphanage. Keywords: Development, Behavior roles social, Teens